SUN-121 Vitamin D Repletion and Sitagliptin Administration is Associated with an Increase in Serum C-Peptide and a Decrease in GAD-65 Antibody and Hemoglobin A1c in a Patient with Latent Autoimmune Diabetes of Adults - Fox, Nicholette (J Endocr Soc, 2019)
Background: Latent Autoimmune Diabetes of Adults (LADA) is characterized by adult onset and circulating autoantibodies e.g. glutamic acid decarboxylase (GAD-65), islet cell antibodies (ICA), and tyrosine phosphate related islet antigen 2 (IA-2). LADA may be misdiagnosed as it has features of both Type 1 (T1DM) and Type 2 (T2DM) diabetes. Dipeptidyl Peptidase-4 (DPP-4) (CD26) is a transmembrane glycoprotein immunomodulator causing a Th1/Th17 dominant milieu while suppressing anti-autoimmune Th2/Treg expression. Th1 and Th17 secrete pro-inflammatory cytokines that mediate β cell autoreactivity. DPP-4 inhibitors (DPP4I), e.g. sitagliptin (S), preserve β cell function, resulting in higher C-peptide levels, suggesting their potential use in LADA. Sustained remission of T1DM was reported in 2 patients with S and Vitamin D (D), leading us to explore their use in LADA. Clinical Case: Our patient is a 45-year-old Hispanic female with a 2 year history of diabetes. She was presumed to have T2DM and was first treated with diet, exercise and metformin, starting in 07/2016. At diagnosis, BMI was 16.16 kg/m² and HbA1c was 10.5% (<5.7). Glipizide and basal/bolus insulin were added in 08/2016. On 10/06/2016 C-peptide was 0.7ng/ml (0.9-7.1) and serum 25-OH-Vitamin D 25.3 ng/ml (30.0-100.0). On 12/11/2017, GAD-65 antibody titer was 54.9nmol/L (<0.02) and ICA was 40 JDF units (<5). Her age of onset, clinical course, and serology were consistent with LADA. In 01/2018, recognizing that she had either T1DM or LADA, S 100mg daily + ergocalciferol 50,000IU weekly were added to her regimen. On 04/05/2018, C-peptide level rose by 29%, GAD-65 antibody fell by 48%, ICA titer remained at 40 JDF units, and A1c fell by 14%. When seen by her primary care provider in April 2018, S was discontinued as the provider thought it was inappropriate for a “T1DM” patient. Subsequently, A1c rose by 7% on 07/10/2018. S was restarted while continuing ergocalciferol on 07/17/2018. Conclusions: This report supports earlier studies suggesting that S+D may be useful options in LADA or T1DM of relatively short duration. Reports of successful treatment of LADA with saxagliptin, and treatment of psoriasis with S suggest that immunomodulation may be a DPP4I class effect useful against autoimmune disease in general. It is likely that DPP4I and D achieve their observed clinical effects via rebalancing the immune system milieu from a Th1/Th17 dominant state toward a Th2/Treg dominant one. Preclinical studies have shown that D supplementation prevents the development of a number of autoimmune conditions, e.g. inflammatory arthritis, autoimmune thyroiditis, and T1DM, which supports the utility of D in the management of LADA. Based on successful prevention of T1DM in NOD mice with S, future trials to prevent T1DM in antibody positive, non-diabetic siblings of T1DM patients with S and/or D will be of interest.